Støvet og skyen - Foucault, Michel (Slagmark - Tidsskrift for idéhistorie, 2018)
This is a translation of Michel Foucault’s text ”La poussière et le nuage” which was written as an answer to the French historian Jacques Léonard’s article ”The historian and the philosopher” where Léonard on some points criticized Foucault’s Discipline and Punish (1975). ”The dust and the cloud” is Foucault’s defense of the kind of history he practices and as it is expressed in Discipline and Punish. The text was published for the first time along with Léonard’s article in Michelle Perrot (ed.), L’Impossible prison – Recherches sur le système péniteniaire au XIXe siècle, Paris: Éditions du Seuil, 1980.